Mechanical twinning of monazite expels radiogenic lead - Fougerouse, Denis; Reddy, Steven; Seydoux-Guiiiaume, A.M.; Kirkland, Chris; Erickson, Timmons; Saxey, David; Rickard, William; Jacob, D.; Leroux, H.; Clark, Chris (2021)
Mechanical twins form by the simple shear of the crystal lattice during deformation. In order to test the potential of narrow twins in monazite to record the timing of their formation, we investigated a ca. 1700 Ma monazite grain (from the Sandmata Complex, Rajasthan, India) deformed at ca. 980 Ma, by electron backscattered diffraction (EBSD), transmission electron microscopy (TEM), and atom probe tomography (APT). APT 208Pb/232Th ages indicate that the twin was entirely reset by radiogenic Pb loss during its formation at conditions far below the monazite closure temperature. The results are consistent with a model where Pb is liberated during rupture of rare earth element-oxygen (REE-O) bonds in the large [REE]O9 polyhedra during twinning. Liberated Pb likely migrated along fast diffusion pathways such as crystal defects. The combination of a quantitative microstructural investigation and nano-geochronology provides a new approach for understanding the history of accessory phases.